PENGARUH CORPORATE GOVERNANCE DAN KOMPENSASI MANAJEMEN TERHADAP MANAJEMEN PAJAK - Juli Ismanto; Natalia Zang (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the influence of corporate governance and management compensation on tax management. Tax management is a dependent variable and corporate governance and management compensation is an independent variable. This type of research is quantitative, with a population of 77 companies this research was conducted on property and real estate sector manufacturing companies listed on the IDX in 2016-2020, a research sample of 8 companies with 5 years of observation, the sample determination method used was purposive sampling. The analysis method uses multiple regression analysis, T test and F test using Eviews 9. The results showed that corporate governance affects tax management and management compensation affects tax management. Meanwhile, corporate governance and compensation management have a simultaneous effect on tax management